2005
DOI: 10.1136/jmg.2005.032433
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of skewed X chromosome inactivation in young patients with familial non-BRCA1/BRCA2 breast cancer

Abstract: Background: A higher frequency of skewed X chromosome inactivation has been reported in a consecutive series of young patients with breast cancer compared with controls of a similar age. Objective: To investigate the X inactivation pattern in patients with familial non-BRCA1/BRCA2 breast cancer (n = 272), BRCA1/BRCA2 germline mutations (n = 35), and sporadic breast cancer (n = 292). Methods: X inactivation pattern was determined by polymerase chain reaction analysis of the highly polymorphic CAG repeat in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 20 publications
2
49
0
Order By: Relevance
“…One study reported a higher frequency of skewed X-inactivation in young breast cancer patients with a family history of breast cancer, but no BRCA1/2 mutations, compared to controls. Howeveer, skewed X-inactivation frequency did not differ significantly between BRCA1/2 mutation carriers and age-matched healthy controls [41]. We did not perform X-inactivation analysis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported a higher frequency of skewed X-inactivation in young breast cancer patients with a family history of breast cancer, but no BRCA1/2 mutations, compared to controls. Howeveer, skewed X-inactivation frequency did not differ significantly between BRCA1/2 mutation carriers and age-matched healthy controls [41]. We did not perform X-inactivation analysis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although less well studied than somatic mutations and LOH, both X chromosome inactivation (42,43) and RNA editing (44) (i.e., a posttranscriptional process that alters the information encoded in gene transcripts, in this case a nsSNV present in the mRNA but not the gDNA) have been previously linked to cancer but not MPM (45). The actual editing is site-specific and occurs through specific mechanisms that are thought to be altered in cancers (44).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about X inactivation and common diseases, except for breast cancer, which has been widely studied, but with inconsistent results. [31][32][33][34][35] …”
Section: Discussionmentioning
confidence: 99%